بنیادنانی پێوەرێک بۆ هەڵسەنگاندنی بەرهەمە هونەریەکانی خوێندکارانی بەشی پەروەردەی هونەر لە بابەتی پەیکەردا - حسین, سه‌رپه‌رشتیار: پ.جواد نعمت; احمد, خوێندكاری دكتۆرا: کامەران محمود (Sulaimani Journal for Humanities, 2023)
The aim of the current study was preparing a criterion for evaluating the sculpture works of art of second year students in the Department of Art Education. According to the nature and objectives of the study, the descriptive method was implemented and the research sample consisted of sculptural works of second year students. The researcher prepared a criterion for evaluating the artistic works of the research sample which consisted of 10 units and 24 items. The tool is finalized after checking its face validity through consulting a number of experts in the field of sculpture and art education and split-half reliability is used through re-evaluating a sample of the works by three experienced academic evaluators and this is done via Pearson Correlation Coefficient.
Keywords: بنیادنان پێوەر هەڵسەنگاندن بەرهەمە هونەریەکان پەروەردەی هونەر پەیکەر